2006
DOI: 10.1097/01.mbc.0000220245.20036.2d
|View full text |Cite
|
Sign up to set email alerts
|

The use of recombinant activated factor VII in the treatment of massive pulmonary hemorrhage in a preterm infant

Abstract: Pulmonary hemorrhage is a rare but well-known complication in preterm infants. We present a case of massive pulmonary hemorrhage in a 9-day-old male infant, successfully treated with intravenous recombinant activated factor VII (rFVIIa) (NovoSeven; Novo Nordisk). The infant was diagnosed with sepsis-related disseminated intravascular coagulation and required ventilator support for respiratory distress syndrome and blood transfusions due to active bleeding from endotracheal tube. After administration of the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…The indications for use of rFVIIa in this cohort are similar to the ones previously reported: pulmonary hemorrhage, gastrointestinal hemorrhage, NEC, subgaleal hemorrhage, subdural hematoma and post-surgical hemorrhage1626. The overall rate of hemostasis in our cohort (72%) is comparable to that of these published reports for infants of varying age groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The indications for use of rFVIIa in this cohort are similar to the ones previously reported: pulmonary hemorrhage, gastrointestinal hemorrhage, NEC, subgaleal hemorrhage, subdural hematoma and post-surgical hemorrhage1626. The overall rate of hemostasis in our cohort (72%) is comparable to that of these published reports for infants of varying age groups.…”
Section: Discussionsupporting
confidence: 87%
“…Hemostasis was achieved in all of the infants with pulmonary hemorrhage (5/5), ranging in gestational age from 24 to 32 weeks, after 1–3 doses of 90 mcg/kg of rFVIIa. Two case reports have described the successful use of rFVIIa for treatment of preterm infants with pulmonary hemorrhage, Cetin et al reported on a single case and Olomu on 2 infants, using doses of 50–120 mcg/kg16,17.…”
Section: Discussionmentioning
confidence: 99%
“…1 There has been an increasing number of reports of the use of rFVIIa to manage uncontrolled hemorrhage in clinical settings outside of these licensed indications, including cardiac surgery, trauma, and obstetrics. [2][3][4] Until recently, there have been few data on off-label use of rFVIIa in pediatric patients, and most have been limited to single case reports [5][6][7] and small or single-center case series, 8,9 including in cardiac surgery, [10][11][12] trauma, 13 and neurosurgery. [14][15][16] There are important differences between pediatric and adult patients with regard to their coagulation system and risk of thromboembolism, susceptibility to bleeding after cardiopulmonary bypass, 17 and the pharmacokinetics of rFVIIa.…”
mentioning
confidence: 98%
“…However, in recent years, off-label rFVIIa use has been increasing in nonhemophilic patients for cessation of hemorrhage [3][4][5][6][7][8][9][10]. Reports of its use in critically ill infants are mostly limited to case reports and small case series [5][6][7][8][9][10]. We performed a large single institutional retrospective review of rFVIIa use in critically ill infants focusing on the safety and efficacy of rFVIIa.…”
mentioning
confidence: 99%